Obstructive Sleep Apnea: From Intermittent Hypoxia to Cardiovascular Complications via Blood Platelets - Gabryelska, Agata; Łukasik, Zuzanna M.; Makowska, Joanna S.; Białasiewicz, Piotr (Frontiers in Neurology, 2018)
Abstract Obstructive sleep apnea is a chronic condition characterized by recurrent episodes of apneas or hypopneas during sleep leading to intermittent hypoxemia and arousals. In recent years the prevalence of the sleep disordered breathing has considerably increased. It is estimated that almost 50% of men and 24% of women suffer from moderate to severe form of the disorder. Snoring, collapse of upper airways and intermittent hypoxia are main causes of smoldering systemic inflammation in patients suffering from obstructive sleep apnea. The systematic inflammation is considered one of the key mechanisms leading to significant cardiovascular complications. Blood platelets, formerly not even recognized as cells, are currently gaining attention as crucial players in the immune continuum. Platelet surface is embedded with receptors characteristic for cells classically belonging to the immune system, which enables them to recognize pathogens, immune complexes and interact in a homo- and heterotypic aggregates. Platelets participate in the process of transcellular production of bioactive lipids by delivering both specific enzymes and substrate molecules. Despite their lack of nucleus, platelets synthetize proteins in a stimuli-dependent manner. Atherosclerosis and consequent cardiovascular complications result from disruption in homeostasis of both of the platelet roles: blood coagulation and inflammatory processes modulation. Platelet parameters, routinely evaluated as a part of complete blood count test, were proposed as markers of cardiovascular comorbidity in patients with obstructive sleep apnea. Platelets were found to be excessively activated in this group of patients, especially in obese subjects. Persistent activation results in enhanced spontaneous aggregability and change in cytokine production. Platelet-lymphocyte ratio was suggested as an independent marker for cardiovascular disease in obstructive sleep apnea syndrome and continuous positive air pressure therapy was found to have an impact on platelet parameters and phenotype. In this literature review we summarize the current knowledge on the subject of platelets involvement in obstructive sleep apnea syndrome and hypothesize the possible pathways in which they contribute to cardiovascular comorbidity.